The Role of Affect Spin in the Relationships between Proactive Personality, Career Indecision, and Career Maturity - Park, In-Jo (Frontiers in Psychology, 2015)
This study attempted to investigate the influence of proactive personality on career indecision and career maturity, and to examine the moderating effects of affect spin. We administered proactive personality, career indecision, and career maturity scales to 70 college students. Affect spin was calculated using the day reconstruction method, wherein participants evaluated their affective experiences by using 20 affective terms at the same time each day for 21 consecutive days. Hierarchical regression analyses showed that proactive personality significantly predicted career indecision and career maturity, even after controlling for valence and activation variability, neuroticism, age, and gender. Furthermore, affect spin moderated the associations of proactive personality with career indecision and maturity. The theoretical and practical implications of the moderating effects of affect spin are discussed.